PERANCANGAN SISTEM INFORMASI PENGELOLAAN BARANG DI GUDANG RPX DOMESTIC STUDI KASUS : PT. ANTAREJA PRIMA ANTARAN - Zahrah Nurlaila; Febri Diandari; Supono (Universitas Methodist Indonesia, 2019)
At this time PT. Antareja Prima Antaran or RPX often experience problems in warehousing such as calculating the time span of stored goods. It takes control of the activity of moving goods and documents to increase the efficiency of warehouse use so that the number and time span of goods are stored at a minimum value or according to the plan. In addition, based on the above problems, a warehouse checking system is made, the Early Warning feature to overcome overload in the warehouse, which is expected by customers not to need to be afraid and worried about the goods in the warehouse that will be sent through the RPX freight forwarder because there will be a checking facility for the goods arriving at the warehouse and the goods to be sent starting from the time the goods are entered and then processed to the place. Business Process Modeling Notation (BPMN) is a technique that enables all parties involved in the process to communicate clearly, correctly, and efficiently. In this way, BPMN defines the semantic notation of the Business Process Diagram (DPB). DPB is a chart based on the 'Flowchart' technique